The Longest Day : Seekers-Return to the Wild #6 - Hunter, Erin (New York, NY : Harper, an imprint of HarperCollinsPublishers, 2016)
When the bears return to Great Bear Lake for the longest day gathering, they find their reunion more challenging than they expected.
Keywords: Bears -- Fiction; Fantasy; Bears -- Fiction; Fantasy fiction